Pengaruh PGI-Triangle (Kemiskinan, Pertumbuhan dan Ketimpangan) Terhadap Akses Pendidikan di Kalimantan Selatan - Herny Yanti; Haifa Lestari (PPJP ULM, 2026)
This study aims to analyze the effect of the PGI-Triangle, consisting of poverty, economic growth, and income inequality, on access to education in South Kalimantan Province. Access to education in this study is measured using the average years of schooling (AYS) as a proxy for educational accessibility. This research employs a descriptive quantitative approach using panel data regression, combining time series and cross-sectional data from 13 regencies/cities in South Kalimantan during the 2014-2024 period. The data used are secondary data obtained from the Central Statistics Agency (BPS) of South Kalimantan Province and analyzed using EViews software. The Chow and Hausman test results indicate that the Fixed Effect Model (FEM) is the most appropriate model. The findings show that poverty and income inequality have a negative and significant effect on access to education, while economic growth has a positive and significant effect. Simultaneously, all variables in the PGI-Triangle significantly affect access to education in South Kalimantan. The coefficient of determination (R²) of 95.94% indicates that variations in access to education can be strongly explained by these three variables. These findings highlight the importance of integrated, inclusive, and equitable development policies to expand equal access to education across South Kalimantan.